2012
DOI: 10.3111/13696998.2012.660254
|View full text |Cite
|
Sign up to set email alerts
|

The cost-effectiveness of pregabalin in the treatment of fibromyalgia: US perspective

Abstract: This model found pregabalin to be cost-effective in treating patients with severe fibromyalgia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…Of the 255 abstracts, based on the inclusion criteria, 56 were selected for further review in full text. In the past 11 years, 55 publications examined economic outcomes associated with pregabalin in FM or neuropathic pain . These 55 publications presented results from 53 studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 255 abstracts, based on the inclusion criteria, 56 were selected for further review in full text. In the past 11 years, 55 publications examined economic outcomes associated with pregabalin in FM or neuropathic pain . These 55 publications presented results from 53 studies.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐one economic evaluations were found for pregabalin in FM and neuropathic pain . The cost‐effectiveness of pregabalin was assessed with cost‐utility, cost‐effectiveness, and cost‐consequence analyses, most often in the US and Western European countries, but also in Canada, Brazil, Colombia, and Mexico (Table S2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They concluded that pregabalin is a cost-effective treatment. In another study in the US [32], a cost-effectiveness analysis was conducted to compare different fibromyalgia management strategies by a decision-analytic model and indirect effectiveness comparison. The results indicated that pregabalin is cost-saving and more effective than placebo, duloxetine, tramadol, milnacipran, and gabapentin.…”
Section: Discussionmentioning
confidence: 99%